2001
DOI: 10.1007/s002590000418
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of leg oedema by dynamic lymphoscintigraphy with intradermal injection of technetium-99m human serum albumin and load produced by standing

Abstract: This study was a preliminary evaluation of the utility of dynamic lymphoscintigraphy with technetium-99m human serum albumin (HSA) and a load produced by standing in the assessment of lymphatic dysfunction in patients with leg oedema. The 71 subjects investigated included 53 patients with lymphoedema, six with venous occlusion alone and five with lymphovenous occlusion, as well as seven normal subjects. After intradermal injection of 99mTc-HSA into an interdigital space in each foot, dynamic scintigrams were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
1
13
0
2
Order By: Relevance
“…In this study, abnormal lymphatic vessels were observed in low extremity lymphedema patients. Moreover, dermal backflow and honeycomb‐like network was observed in some patients, which may be due to opacification of multiple tiny peripheral lymphatic vessels or due to extravasation of the contrast agent . The morphologic changes of the LV in this study were consistent with other reports .…”
Section: Discussionsupporting
confidence: 90%
“…In this study, abnormal lymphatic vessels were observed in low extremity lymphedema patients. Moreover, dermal backflow and honeycomb‐like network was observed in some patients, which may be due to opacification of multiple tiny peripheral lymphatic vessels or due to extravasation of the contrast agent . The morphologic changes of the LV in this study were consistent with other reports .…”
Section: Discussionsupporting
confidence: 90%
“…Using lymphoscintigraphy, the diagnosis of lymphatic dysfunction is based on abnormal radiotracer distribution and/or delayed or absent lymphatic flow [8,9]. Lymphoscintigraphy permits the detection of retarded tracer transport even in mild lymphoedema without morphological abnormalities [9] because impaired lymphatic function is visualised before morphological changes appear [10]. Therefore it lends itself more readily to repeated studies for follow-up than other available tests [11].…”
Section: Resultsmentioning
confidence: 99%
“…The cross-over filling of the contralateral pelvic lymph nodes proves the patency of the graft the diagnostic modality of choice for the assessment of functional disturbances of lymphatic vessels [8]. Using lymphoscintigraphy, the diagnosis of lymphatic dysfunction is based on abnormal radiotracer distribution and/or delayed or absent lymphatic flow [8,9]. Lymphoscintigraphy permits the detection of retarded tracer transport even in mild lymphoedema without morphological abnormalities [9] because impaired lymphatic function is visualised before morphological changes appear [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations